Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1097/01.aids.0000247566.57762.b2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of sexual partner's HIV serostatus and serosorting practices in a California population-based sample of men who have sex with men

Abstract: This population-based survey documented the extent to which MSM know their partners' serostatus and practice serosorting behaviors. The findings emphasize the need for studies to report serocordant and serodiscordant unprotected anal intercourse separately, as the former presents significant lower risk of HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 35 publications
3
62
1
3
Order By: Relevance
“…[8][9][10] Negotiated safety agreements have been described among men who have sex with men (MSM) as strategies for selectively practicing condomless anal intercourse (CAI) while maintaining sexual pleasure and intimacy within relationships. [11][12][13][14][15][16][17] While intended to reduce HIV risk, such strategies may fail in practice due to factors such as inaccurate assessment of individual and partner serostatus, infrequent testing, failure to maintain the agreement, and lack of protection against STIs. [18][19][20][21] Shortcomings in assessing partner HIV risk have also been reported among heterosexuals.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Negotiated safety agreements have been described among men who have sex with men (MSM) as strategies for selectively practicing condomless anal intercourse (CAI) while maintaining sexual pleasure and intimacy within relationships. [11][12][13][14][15][16][17] While intended to reduce HIV risk, such strategies may fail in practice due to factors such as inaccurate assessment of individual and partner serostatus, infrequent testing, failure to maintain the agreement, and lack of protection against STIs. [18][19][20][21] Shortcomings in assessing partner HIV risk have also been reported among heterosexuals.…”
Section: Introductionmentioning
confidence: 99%
“…Some men restrict their UAI only to men whom they believe to be HIV seroconcordant (Parsons et al 2005; Van de Ven et al 1998;Mao et al 2006;Xia et al 2006), while between serodiscordant partners, some men use strategic positioning, whereby HIV-negative men take the insertive position and HIV-positive men take the receptive position during UAI (Parsons et al 2005; Van de Ven et al 2002). Use of such strategies depends on clear reliable knowledge of sexual partners' HIV serostatus.…”
Section: Introductionmentioning
confidence: 99%
“…Trends in unprotected anal intercourse with casual partners (UAIC) known (or assumed) to be of opposite HIVstatus (serodiscordant) have rarely been documented, mostly due to a lack of data about serostatus of casual sex partners, particularly among HIV-negative gay men. Among HIV-negative men, serodiscordant unprotected anal intercourse with casual partners, has usually involved very small numbers of men (Golden et al 2004;Xia et al 2006). Chen et al (2003) examined 'potentially' serodiscordant unprotected anal intercourse in San Francisco and reported an increase from 1999 to 2001 in 'unprotected anal intercourse with two or more partners of unknown HIV serostatus'.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2003) examined 'potentially' serodiscordant unprotected anal intercourse in San Francisco and reported an increase from 1999 to 2001 in 'unprotected anal intercourse with two or more partners of unknown HIV serostatus'. More recently, Xia et al (2006) explored serodiscordant unprotected anal intercourse with both primary and most recent secondary (casual) partners and found that no HIV-negative men reported serodiscordant unprotected anal intercourse with their most recent secondary partner. Serodiscordant unprotected anal intercourse remains self-evidently the practice of greatest risk for HIV transmission among MSM, but there is still a lack of evidence about this behaviour.…”
Section: Introductionmentioning
confidence: 99%